PENGARUH KUALITAS PELAYANAN APARATUR SIPIL NEGARA TERHADAP KEPUASAN MASYARAKAT ATAS PENGELOLAAN PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN PADA BADAN PENDAPATAN DAERAH KABUPATEN KARAWANG - Santi Aryanti; Muhammad Harun Alrasyid (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2021)
The purpose of this study was to determine the effect of service quality variables, on community satisfaction with land and building tax management in rural and urban areas in regional revenue agencies in Karawang district. The methodology used in this study uses a quantitative approach with an explanatory type to answer hypotheses, with data analysis techniques using simple linear regression statistical tests. The results of the analysis show that there is an influence between service quality and community satisfaction based on results based on results (R) of 0.672, so this situation indicates a strong and significant positive (relationship) / influence between the personnel service quality variable on the Community Satisfaction variable based on the assessment criteria criteria and The coefficient of determination (R2) is 0.452, for the level of Community Satisfaction with the Service Quality of State Civil Servants in the Management of PBB P2 at the Regional Revenue Agency of Karawang Regency, based on the Community Satisfaction Survey it is included in category B, namely Good with a conversion value of 76.67, while the elements Services that fall into the awake category are service time, fees / rates, executive competence, executor behavior, complaint handling, and input, while what needs to be improved are requirements, systems, procedures and procedures, product specifications for the type of service and facilities and infrastructure.